2018
DOI: 10.1093/sleep/zsy085
|View full text |Cite
|
Sign up to set email alerts
|

The association between obstructive sleep apnea and metabolic abnormalities in women with polycystic ovary syndrome: a systematic review and meta-analysis

Abstract: OSA is associated with obesity and worse metabolic profiles in women with PCOS. However, whether the effects of OSA are independent of obesity remain unclear. As OSA is a treatable condition, research focused on the independent effects of OSA on key clinical outcomes in women with PCOS, including fertility, psychological health, type 2 diabetes, and cardiovascular risk, is lacking and needed. PROSPERO registration number: CRD42016048587.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 43 publications
(33 reference statements)
0
20
0
Order By: Relevance
“…In a recent systematic review and meta-analysis, OSA was associated with worse metabolic profile in women with PCOS [33]. However, despite its high prevalence and clinical implications, OSA often remains undiagnosed particularly in women [19,34].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent systematic review and meta-analysis, OSA was associated with worse metabolic profile in women with PCOS [33]. However, despite its high prevalence and clinical implications, OSA often remains undiagnosed particularly in women [19,34].…”
Section: Introductionmentioning
confidence: 99%
“…In another meta-analysis from our group comparing women with PCOS and OSA vs women with PCOS only showed that the earlier group had higher BMI (mean difference: 6.01 kg/m 2 , 95% CI: 4.69-7.33), waist circumference (MD: 10.93 cm, 95% CI: 8.03-13.83), IR (HOMA-IR: MD = 2.23, 95% CI: 1.41-3.06; I 2 = 0%), systolic BP (10.8 mmHg 95% CI: 6.21-15.39), diastolic BP (4.63 mmHg 95% CI: 1.06-8.21), impaired glucose tolerance (2 h plasma glucose on OGTT: MD = 2.23, 95% CI: 0.67-2.11, I 2 = 0%) and worse lipids profile (higher total cholesterol, LDL and triglycerides and lower HDL) compared to the alter group (349). The androgen levels were not different between the two groups but hirsutism was worse in the OSA group (349). However, these studies included were relatively small, at high risk of selection bias, and did not account for important potential confounders such as obesity (349).…”
Section: Osa and Polycystic Ovarian Syndrome (Pcos)mentioning
confidence: 94%
“…The androgen levels were not different between the two groups but hirsutism was worse in the OSA group (349). However, these studies included were relatively small, at high risk of selection bias, and did not account for important potential confounders such as obesity (349).…”
Section: Osa and Polycystic Ovarian Syndrome (Pcos)mentioning
confidence: 98%
“…Similarly, the effects of OSA on important clinical outcomes in women with PCOS including QoL, risk of type 2 diabetes (T2DM) or cardiovascular disease (CVD) remain unknown. 6 In this study, we hypothesized that women with PCOS and OSA have a more severe phenotype of PCOS and lower QoL compared with women with PCOS without OSA. Our primary aim was to examine the relationship between OSA and QoL in women with PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 A better understanding of the relationship between PCOS and OSA is important, as OSA may contribute to The relationship between obstructive sleep apnoea and quality of life in women with polycystic ovary syndrome: a crosssectional study the clinical phenotype of PCOS, which can be at least partly corrected by continuous positive airway pressure (CPAP) treatment. 1,6 Excessive daytime sleepiness (EDS) is often seen in patients with OSA and is attributed to factors including intermittent night-time hypoxaemia, sleep fragmentation and changes in sleep architecture and quality. 7 However, many patients with OSA do not have EDS, and EDS is also commonly seen in the general population.…”
Section: Introductionmentioning
confidence: 99%